Multifunctional Nanofibrous Dressing with Antimicrobial and Anti-Inflammatory Properties Prepared by Needle-Free Electrospinning - Laura Victoria Schulte-Werning; Anjanah Murugaiah; Bhupender Singh; Mona Johannessen; Rolf Einar Engstad; Nataša Škalko-Basnet; Ann Mari Holsæter (MDPI AG, 2021)
An active wound dressing should address the main goals in wound treatment, which are improved wound healing and reduced infection rates. We developed novel multifunctional nanofibrous wound dressings with three active ingredients: chloramphenicol (CAM), beta-glucan (βG) and chitosan (CHI), of which βG and CHI are active nanofiber-forming biopolymers isolated from the cell walls of Saccharomyces cerevisiae and from shrimp shells, respectively. To evaluate the effect of each active ingredient on the nanofibers' morphological features and bioactivity, nanofibers with both βG and CHI, only βG, only CHI and only copolymers, polyethylene oxide (PEO) and hydroxypropylmethylcellulose (HPMC) were fabricated. All four nanofiber formulations were also prepared with 1% CAM. The needle-free NanospiderTM technique allowed for the successful production of defect-free nanofibers containing all three active ingredients. The CAM-containing nanofibers had a burst CAM-release and a high absorption capacity. Nanofibers with all active ingredients (βG, CHI and CAM) showed a concentration-dependent anti-inflammatory activity, while maintaining the antimicrobial activity of CAM. The promising anti-inflammatory properties, together with the high absorption capacity and antimicrobial effect, make these multifunctional nanofibers promising as dressings in local treatment of infected and exuding wounds, such as burn wounds.